2022
DOI: 10.3390/ijerph192114027
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Decision-Making for Appendectomy in Kosovo: A Conjoint Analysis

Abstract: Objective: The objective was to investigate the association of clinical attributes with decision making for performing appendectomy and making preoperative preparations for appendectomy. Method: A conjoint analysis with 17 clinical scenarios was executed with surgeons employed at public hospitals in Kosovo. Setting: The study was conducted at two public hospitals in Kosovo that have benefited from quality-improvement interventions. Participants: The participants included 22 surgeons. Outcome measures: The prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
2
3
0
Order By: Relevance
“…This fact does not come as a surprise, considering that it is common in low-income and low-middle-income countries [ 37 ], where opportunities for professional advancement are limited. Similar results were found in another conjoint analysis performed in Kosovo investigating decision-making for appendectomy and pre-operative preparation for appendectomy [ 27 ].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This fact does not come as a surprise, considering that it is common in low-income and low-middle-income countries [ 37 ], where opportunities for professional advancement are limited. Similar results were found in another conjoint analysis performed in Kosovo investigating decision-making for appendectomy and pre-operative preparation for appendectomy [ 27 ].…”
Section: Discussionsupporting
confidence: 86%
“…Standard conjoint analysis methodology was used to design and implement this study, including five steps: defining attributes, assigning attribute levels, creating scenarios, obtaining preference data, and estimating model parameters. The conjoint analysis design is consistent with previous studies [ 24 , 25 , 27 ].…”
Section: Methodssupporting
confidence: 87%
See 1 more Smart Citation
“…It confirms many publicly known facts about the management of NCDs that are valid for most of the healthcare provided in the country. For example, studies have reported that the system is underfunded, [ 4 , 11 , 87 ] care availability is limited in quality and quantity, [ 4 , 83 ] issues exist relating to availability and impact of the application of clinical standards [ 4 , 15 , 84 ], and there are issues with supply with the workforce [ 11 , 88 ]. This review highlights the issues with a defragmented system of provision of NCD care, as well as efforts in the function of improvement of the existing situation.…”
Section: Discussionmentioning
confidence: 99%
“…Private health expenditure, almost entirely in the form of out-of-pocket payments by households at the point of service, contributes an estimated 40 percent of total spending in the sector [ 10 , 11 ]. The application of standards of care is limited [ 15 ]. Medical practice is left to physician education, experience, and willingness to perform clinical procedures.…”
Section: Introductionmentioning
confidence: 99%